06 Early subcortical amyloid deposition in familial Alzheimer's disease is accompanied by changes in tissue volume and diffusivity. Issue 3 (15th February 2011) - Ryan, N S; Okello, A; Knight, W D; Lehmann, M; Malone, I; Ridgway, G R; Ourselin, S; Brooks, D J; Rossor, M N; Fox, N C
Abstract : Background: In FAD, 11C-Pittsburgh compound B PET studies have revealed the striatum and thalamus to be the earliest sites of amyloid deposition. We investigated whether these regions also show changes in volume or diffusivity. Methods: Twelve Presenilin 1 (PSEN1) mutation carriers (MCs) and sixteen controls underwent cognitive assessment, volumetric and diffusion MRI. Six MCs were symptomatic, six presymptomatic. Scans were segmented using Freesurfer(v4.4.0) into cortical and subcortical regions, which were registered to the diffusion data. Linear regression models assessed regional group differences in volume and diffusion indices. Results: After adjusting for gender, age and total intracranial volume, presymptomatic MCs demonstrated significantly smaller volumes of the right caudate by 0.51ml (p=0.004) and left caudate by 0.44 ml (p=0.046) compared to controls. Thalamic fractional anisotropy (FA) was increased on the left (p=0.018) and to a lesser degree on the right (p=0.14). Symptomatic MCs showed widespread volume loss and decreased FA in the brain compared to controls, however the increased left thalamic FA persisted (p=0.03) with weaker evidence of increased right thalamic FA (p=0.22). Conclusions: Volume and diffusivity changes in the striatum and thalamus appear to occur presymptomatically in PSEN1 MCs. These areas demonstrate early amyloid deposition, which may cause differing microstructural alterations depending on the neuronal populations affected and the disease stage.